Impact of land surface temperature variability and population growth on ecosystem services in the central districts of Antalya - Betül Tülek; Gamze Seçkin Gündoğan (Ain Shams Engineering Journal)
The change in land cover associated with urbanization modifies the microclimate, leading to urban heat islands. As cities grow rapidly, many areas crucial for biodiversity are damaged day by day, and this negatively affects the urban ecosystem services (ES). This research examines the macroform change in parallel with the population increase over the years in the 5 central districts of the Province of Antalya (Konyaaltı, Döşemealtı, Kepez, Muratpaşa and Aksu), which were selected as the study area. In this context, Land Surface Temperature (LST) change data and the Normalized Difference Vegetation Index (NDVI) between 2007–2022 were analyzed and ES effects were revealed. The relationship between LST and NDVI was analyzed by correlating the LST and NDVI with the ES provided from the area through LULC data. While a high negative correlation was observed between the LST and NDVI dataset, the increase in residential, industrial and bare areas with increasing population between the specified years and the decrease in vegetation cover were established as the main parameter here. As a result, although the population growth in urban areas continues, the increase in ES and green infrastructure elements in urban settlements will lead to a decrease in LST values.